The value of designers' creative practice within complex collaborations. (September 2016) - Bowen, Simon; Durrant, Abigail; Nissen, Bettina; Bowers, John; Wright, Peter
Abstract : This paper reports a case study investigating the productive value of designers ' creative practice within complex academic-industrial collaborations in which a designer's practice had a formative role. Adopting a pragmatic approach, collaborators' experiences of this project were reconstructed through interviews and 'annotated timelines.' Collaborators were found to value the designer's work in responding to their particular concerns whilst also opening up new possibilities. This paper discusses how such benefit is attributable to the ' designerly thinking ' of skilled designers, shifting the focus of work from problem-solving to problematisation and enabling participants to collectively formulate concerns, roles, and potentialities. The paper concludes that designers ' creative practice can enable collaborative projects to build upon and transcend participants' expertise and expectations through 'creative exchange.' Highlights: Creative practice can be a means to manage complex collaborations. Asymmetrical participation in creative activities need not imply an unequal collaboration. Creative practice fosters constructive dialogue in academic-industry collaborations. Creative practice creates artefacts and productive collaborative relationships.